2018
DOI: 10.2355/isijinternational.isijint-2017-456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaO/Al<sub>2</sub>O<sub>3</sub> Ratio of Ladle Slag on Formation Behavior of Inclusions in Mn and V Alloyed Steel

Abstract: The effect of CaO/Al 2 O 3 ( = C/A) ratio of the ladle slag on the formation behavior of non-metallic inclusions in the Mn-V-alloyed steel was investigated using both the experimental method and refractory-slagmetal-inclusion (ReSMI) multiphase reactions simulation. The formation behavior of inclusion was strongly affected by the activity of MgO in the initial slag at the early stage of the reaction. However, since the MgO activity converged to unity due to MgO dissolution from refractory to slag during the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…[93,112,113] The changes in the CaO/Al 2 O 3 (= C/A) ratio of the ladle slag on the inclusion evolution in the Mn and V alloyed steel were successfully simulated by HURG, as shown in Figure 24. [92] The symbols in Figure 24(a) represent the Mg and Ca traces in molten steel according to the reaction time calculated using the ReSMI model. Alumina inclusion is stable at the initial stage of the reaction.…”
Section: Excel Is a Trademark Of Microsoft Corporationmentioning
confidence: 99%
See 1 more Smart Citation
“…[93,112,113] The changes in the CaO/Al 2 O 3 (= C/A) ratio of the ladle slag on the inclusion evolution in the Mn and V alloyed steel were successfully simulated by HURG, as shown in Figure 24. [92] The symbols in Figure 24(a) represent the Mg and Ca traces in molten steel according to the reaction time calculated using the ReSMI model. Alumina inclusion is stable at the initial stage of the reaction.…”
Section: Excel Is a Trademark Of Microsoft Corporationmentioning
confidence: 99%
“…(a) Trajectory of inclusions shown in the phase stability diagram with iso-oxygen contours and (b) SEM image of inclusions at the early (5 min) and final (30 to 90 min) stages of the refining reaction in the Fe-0.4C-0.7Si-1.4Mn-0.2V-0.015Al (mass pct) melt containing Mg and Ca at 1873 K (1600°C). Reprinted with permission from Ref [92]…”
mentioning
confidence: 99%
“…20,21) The effect of the slag composition on the formation of spinel-type inclusions has been investigated to improve the purity of liquid steel. [22][23][24][25] Formation of V-rich spinel phase in CaO-SiO 2 -MgO-FeO t -Al 2 O 3 -V 2 O 3 -P 2 O 5 slags at 1 573 K has been discussed to separate the vanadium-concentrating phase. 26) Meanwhile, many researchers have reported that the suitable of crystallization temperatures of spinels in vanadium-containing slags was 1 373-1 573 K, but the vanadium-containing slags's viscosity could significantly worsen at temperatures below 473 K. 18,19,[27][28][29] In addition, the evolution of the bath temperature during the extraction process is at the range of 1 473-1 673 K, and the smelting time is merely 15 min.…”
Section: Crystallization Behavior and Growth Mechanisms Of Spinel Crymentioning
confidence: 99%
“…This provides the stable oxide phases in the FeCrNiMnCo alloy melt containing aluminum and oxygen. This kind of phase stability diagram is widely used to predict the composition of non-metallic inclusions in molten steels [49][50][51][52][53]. An air exposure to alloy melt has an influence not only on the chemistry but also on the size distribution of inclusion particles.…”
Section: Characterization Of Non-metallic Inclusionsmentioning
confidence: 99%